The hidden blood loss and its factors in patients undergoing minimally invasive knee arthroscopy - Li, Sheng; A, Liang (Frontiers in Surgery, 2022)
Background: With respect to knee arthroscopy, assessing amount of hidden blood loss is of great importance in order to avoid aforementioned potential complications. Current study aims to investigate the hidden blood loss and its factors in patients underwent minimally invasive knee arthroscopy. METHODS: Consecutive patients with knee joint injury, who underwent arthroscopic minimally invasive treatment, were enrolled from January 2019 to November 2020 were retrospectively studied. The patient’s demographic information, medical history and biochemical parameters were collected, respectively. The hidden blood loss was calculated. Multivariate linear regression analysis was used to confirm independent factors associated with hidden blood loss. Results: Finally, a total of 100 patients aged 44.7813.67 (range, 17-6) years were reviewed, with a substantial amount of 387.02252.56 (rang, 18.89-1130.06) ml hidden blood loss occurred after minimally invasive knee arthroscopy. Univariate analysis showed that hidden blood loss was negatively correlated with age, gender, postoperative hemoglobin, and postoperative hematocrit (all P<0.05), while it was positively correlated with body mass index (BMI), length of hospital stay, preoperative red blood cells, preoperative hemoglobin, preoperative hematocrit, blood volume, and the presence of medical conditions (all P<0.05). Further multivariate linear regression indicated that preoperative hematocrit, blood volume and postoperative hematocrit were independent factors associated with actual blood loss, and preoperative hematocrit, blood volume, postoperative hematocrit and gender were independent factors associated with hidden blood loss, respectively (all P<0.05). Conclusion: Preoperative hematocrit, preoperative blood volume, postoperative hematocrit and gender are the influencing factors of hidden blood loss in patients undergoing minimally invasive treatment under knee arthroscopy. Hidden blood loss and its factors should be paid more attention to during the perioperative period.